Procedural Application of Know Your Customer by Notary - Michelle Hibono; Benny Djaja (Faculty of Law, University of Mataram, 2026)
Money laundering poses significant threats to economic stability and the integrity of financial and legal systems. As part of the anti-money laundering framework, notaries in Indonesia are required to implement the Know Your Customer (KYC) principle when providing certain legal services. This study aims to analyze the legal framework and procedural implementation of KYC by notaries in accordance with applicable regulations. This research employs a normative legal research method, using a statutory approach to examine relevant laws and regulations. The findings show that KYC implementation by notaries involves several stages, including client identification, verification of information and documents, risk assessment of clients and beneficial owners, transaction monitoring, record-keeping, and reporting suspicious financial transactions to the Financial Transaction Reports and Analysis Center (PPATK). Through these procedures, notaries play an important role as gatekeepers, helping prevent money laundering and strengthening transparency and accountability within the legal system.